Renoprotective Effect of the Shen-Yan-Fang-Shuai Formula by Inhibiting TNF-α/NF-κB Signaling Pathway in Diabetic Rats - Jie Lv; Zhen Wang; Ying Wang; Weiwei Sun; Jingwei Zhou; Mengdi Wang; Wei Jing Liu; Yaoxian Wang (Journal of Diabetes Research)
Diabetic kidney disease (DKD) is the leading cause of end-stage kidney disease, and satisfactory therapeutic strategies have not yet been established. The Shen-Yan-Fang-Shuai Formula (SYFSF) is a traditional Chinese formula composed of Astragali radix, Radixangelicae sinensis, Rheum officinale Baill, and four other herbs. It has been widely used as an effective treatment for DKD patients in China. However, little is known about the molecular mechanisms underlying SYFSF’s renoprotection. In this study, we compared the protective effect of SYFSF to irbesartan on the histology and renal cells in type 2 DKD rat model and high-glucose (HG) cultured mesangial cells, respectively. We found that SYFSF could significantly decrease urinary albumin, cholesterol, and triglyceride. And a decrease in serum creatinine was also found in SYFSF-treated group compared with irbesartan-treated rats. In addition, SYFSF inhibited the interstitial expansion and glomerulosclerosis in diabetic rats. Notably, SYFSF markedly downregulated the expression of MCP-1, TGF-β1, collagen IV, and fibronectin in diabetic rat models and HG-induced mesangial cell models. The renoprotection was closely associated with a reduced expression of TNF-α and phosphorylated NF-κBp65. Our study suggests that SYFSF may ameliorate diabetic kidney injury. The observed renoprotection is probably attributable to an inhibition of inflammatory response and extracellular matrix (ECM) accumulation mediated by TNF-α/NF-κBp65 signaling pathway.